(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Today it is impossible to imagine a person without a mobile phone; often people have not one, but several “mobile phones”. This work was carried out among students of a higher educational institution (Tashkent Medical Academy) and it was revealed that 100% of students had cell phones. This study examined the prevalence and use of cellular communications among students, the influence of electromagnetic fields emitted by mobile phones and other electronic devices on their health and sleep. The adverse effects of electromagnetic radiation from electronic devices have been identified